Analysis of Factors Affecting the Open Unemployment Rate (UOR) 2022 : A Case of Banten in Indonesia - Aqilla Haya; Risma Dwi Lestari; Tengku Mashitah Crisanty (Proceedings of The International Conference on Data Science and Official Statistics, 2023)
Unemployment is one of the many economic problems. One type of unemployment is open unemployment. The Open Unemployment Rate (UOR) in Banten Province has the largest rate in Indonesia. In this study, exploratory factor analysis was used with the aim of finding out the factors that contribute to UOR in Banten Province. The data source used is secondary data obtained from publications by Badan Pusat Statistik. Factor 1 (human development) includes the Human Development Index, Economic Growth, Population Growth Rate, Literacy Rate and Mean Years of Schooling (MYS) and Factor 2 (population) consists of only one variable, that is total population. The results of this research show that total population, HDI, and MYS have the largest contribution to UOR in Banten Province. It is hoped that the government can increase business opportunities, employment opportunities and mature human development planning to reduce UOR in Banten Province.